Melt Shear Viscosity of Original and Recycled Pet in Wide Range Shear Rate Melt Shear Viscosity - Bata, Attila; Toth, Gergely; Belina, Karoly (Communications - Scientific letters of the University of Zilina, 2017)
Among the plastic materials, the PET is the most often used one. Collecting of the material to be recycled is partially solved. This way we have great quantity of regrinded PET. During the regrinding the structure of molecules changes, and these properties can be measured by rheological methods. Polymer melts are-newtonian fluids and the flow curves of the materials can be used to characterize the molecular weight and the molecular weight distribution. This research is focused on the characterization of original and regrinded PET materials. Inherent viscosities (IV) were determined to characterize the materials. Flow curves of pure and blended materials were measured at different temperatures.